Digital light processing 3D printed silk fibroin hydrogel for cartilage tissue engineering - Hong, Heesun; Seo, Ye Been; Kim, Do Yeon; Lee, Ji Seung; Lee, Young Jin; Lee, Hanna; Ajiteru, Olatunji; Sultan, Md Tipu; Lee, Ok Joo; Kim, Soon Hee; Park, Chan Hum (Biomaterials, 2020)
Three-dimensional printing with Digital Lighting Processing (DLP) printer has come into the new wave in the tissue engineering for regenerative medicine. Especially for the clinical application, it needs to develop of bio-ink with biocompatibility, biodegradability and printability. Therefore, we demonstrated that Silk fibroin as a natural polymer fabricated with glycidyl-methacrylate (Silk-GMA) for DLP 3D printing. The ability of chondrogenesis with chondrocyte-laden Silk-GMA evaluated in vitro culture system and applied in vivo. DLP 3D printing system provided 3D product with even cell distribution due to rapid printing speed and photopolymerization of DLP 3D printer. Up to 4 weeks in vitro cultivation of Silk-GMA hydrogel allows to ensure of viability, proliferation and differentiation to chondrogenesis of encapsulated cells. Moreover, in vivo experiments against partially defected trachea rabbit model demonstrated that new cartilage like tissue and epithelium found surrounding transplanted Silk-GMA hydrogel. This study promises the fabricated Silk GMA hydrogel using DLP 3D printer could be applied to the fields of tissue engineering needing mechanical properties like cartilage regeneration.